Hearing Screening Age Considerations for Adults: National Health and Nutrition Examination Survey - Jordan, Jaxon; Baiduc, Rachael R.; Spankovich, Christopher (Journal of the American Academy of Audiology, 2022)
Background The United States Preventative Service Taskforce recently determined that there was insufficient evidence to recommend hearing screening in adults.Purpose To determine the age to screen adults in the U.S. for hearing loss and identify factors related to increased odds of hearing loss.Research Design Epidemiological Cross-Sectional Study.Study Sample Data from 3,409 individuals aged 20–69 years(y) were analyzed from the 1999–2000 and 2000–2002 cycles of the National Health and Nutrition Examination Survey (NHANES).Data Collection and Analysis Hearing sensitivity from 0.5–8 kHz was assessed and hearing loss was defined as pure tone average 0.5, 1, 2, 4 kHz (PTA4) > 15 dBHL for the worse ear. Thresholds were examined separately for men and women in 2-year intervals. A multivariate ordinal regression model adjusting for age, sex, race/ethnicity, and education was used to examine relationship to determinants.Results Slight (>15 dBHL) hearing loss based on threshold at a single audiometric frequency was first evident in males aged 28–29y. For females, this occurred at age 34–35y. The age at which average PTA4 increased above 15 dBHL (slight hearing loss) was 46–47y for males and 56–57y for females. Multivariate ordinal regression revealed the following “high risk” factors: increased age, male sex, tinnitus, perceived hearing loss, and diabetes.Conclusions For the function of primary prevention, these data suggest screening should initiate at ∼30y for males and 35y for females, the ages when average hearing thresholds at a single frequency can be classified as slight hearing loss. For secondary prevention, the recommended screening ages are higher – 45y for males and 55y for females. Hearing screening is recommended for asymptomatic adults, especially those with high risk factors. Our results also highlight the limitations of PTA4 in identifying early indices of hearing loss.
Keywords: hearing loss; epidemiology; screening